“Se dez vidas tivesse, dez vidas daria”: O Movimento Revolucionário Tiradentes e a participação da classe trabalhadora na resistência (1964-1971) - Carvalho, Yuri Rosa de (2014)
The participation of the working class in the process of resistance to the National Security Dictatorship has been majorly silenced by the historiography that deals with the subject. Placed in second plan, it has been strengthened a representation of resistance that projects as protagonists of history young students of the middle classes, immersed in a quixotic adventure set against the established dictatorial power. With no chance of success and without the ability to understand the reality that they intended to revolutionize, the guerrilla organizations that led the armed resistance were supposedly the result of voluntarism of intellectuals and the absence of effective participation of workers. However, the working class was present in the resistance since the Coup of 31 March of 1964, organizing in various cities in various regions of Brazil, work stoppages and strikes against the overthrow of the constitutional government of João Goulart. When the dictatorship gave clarity signs that served the interests of the Brazilian dominating classes, repressing and disorganizing the unions, the working class has taken steps toward reorganization, creating, through the paralelistic agency, commissions and committees of factory which established networks of solidarity between professional categories of the same region, in a process catalyzed by the fight against wage squeeze that led to major demonstrations and the great strikes of Contagem and Osasco in 1968. With the limitations imposed by the IA-5, published in late 1968 in response to the reorganization of the working class, it left, as direct coping strategy that enabled victory in the short term against National Security Dictatorship, the insertion to the armed resistance, in which many workers would act, even in prominent positions. The Revolutionary Movement Tiradentes (RMT) was an example of an organization mostly composed of militants coming from the working class, putting into practice the revolutionary actions that looked for financing the implementation of the guerrilla in the field, but also sabotaging strategic points of Dictatorship, and undermine the image of "democracy" and legitimacy to the dictatorial State attempted to print. With an internal structure that has adapted to the events of that time and established guiding principles, the RMT participated in actions of expropriation, leafleting, propaganda, kidnapping of the Japanese consul in São Paulo and ―justicizing‖ the industrial Henning Boilesen, in response to the murder of its main leadership Devanir José de Carvalho, occurred in April 1971 when the organization was already surrounded by organs of repression.